“IMPACTO DEL PROYECTO RUTA DEL RIO DEL CANTÓN QUEVEDO EN LA GENERACIÓN DE EMPLEO, AÑO 2024” - Romero Maiquiza, Dixon Bladimir (2024)
This research was conducted with the aim of determining the impact of the "Ruta del Rio" project in Quevedo on employment generation in the year 2024. The population considered for this study consisted of all business owners located in the Ruta del Río area in Quevedo, totaling 25 people. A questionnaire with 11 questions was designed in Google Forms and used as the instrument for the survey application. The results revealed that the demographic analysis shows that most of the business owners along the Ruta del Río are young adults, predominantly in the 30 to 40 age group. The most common commercial activities include entertainment, food services, and recreation, highlighting a diverse range of offerings that attract different segments of the population. Entertainment activities are the most prevalent among the surveyed businesses, followed by food service and recreation establishments. This diversification indicates an effective strategy to attract and retain a diverse clientele, which is crucial for economic success in a dynamic tourist environment like the Ruta del Río. Perceptions of tourism promotion are mixed, with a majority believing that current initiatives could be improved. To promote sustainable tourism development, it is recommended to implement strategies that increase the visibility of businesses, take advantage of local tourism events and activities, and improve basic infrastructure to mitigate the identified challenges.